Population dynamics of DENV-1 genotype V in Brazil is characterized by co-circulation and strain/lineage replacement - Drumond, Betania Paiva; Mondini, Adriano [UNESP]; Schmidt, Diane J.; Bosch, Irene; Nogueira, Mauricio Lacerda (Springer Wien, 2012)
Following successive outbreaks of dengue fever caused predominantly by dengue virus (DENV) 2 and 3, DENV-1 is now the primary serotype circulating in Brazil. We sequenced and analyzed Brazilian DENV-1 genomes and found that all isolates belong to genotype V and are subdivided into three lineages, which were introduced during four different events. The first introduction occurred in 1984-85, the second in 1997-99, and the third and fourth occurred from 2004 to 2007. These events were associated with an increase in genetic diversity but not with positive selection. Moreover, a potential new recombinant strain derived from two distinct lineages was detected. We demonstrate that the dynamics of DENV-1 in Brazil is characterized by introduction, movement, local evolution, and lineage replacement. This study strengthens the relevance of genotype surveillance in order to identify, trace, and control virus populations circulating in Brazil and Latin America.